2018
DOI: 10.1186/s40623-018-0962-x
|View full text |Cite
|
Sign up to set email alerts
|

A new five-wavelength photometer operated in Tromsø (69.6°N, 19.2°E)

Abstract: A new five-wavelength photometer was developed and installed at the EISCAT Tromsø site (69.6°N, 19.2°E) in January 2017. The photometer consists of two units: an optical unit and a control unit together with a PC. The photometer is capable of simultaneously observing auroral emissions with five wavelengths. A uniqueness of the present system is its capability of precise pointing, which enables pointing the photometer at the field-aligned position using a star image obtained with a coaxial digital camera. Anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Since 2011, Nikon digital cameras (D5000, D5100 and D7200) have been capturing all-sky images almost every night from September to March with a temporal resolution of less than one minute at Ramfjordmoen Research Station in Tromsø, Norway (69.6 • N, 19.2 • E); the station is operated by the UiT -the Arctic University of Norway. These images were not originally planned to be used for a statistical analysis of the auroras, as they were obtained to evaluate weather conditions during the acquisition of atmospheric temperature/wind observations using a sodium LIDAR [37][38][39][40] and multi-wavelength observations of auroras using a photometer [41][42][43] . The digital cameras used were D5000 during 2010-2014, D5100 during 2015, and D7200 during 2016-2021.…”
Section: Optical Observations In Tromsø Norwaymentioning
confidence: 99%
“…Since 2011, Nikon digital cameras (D5000, D5100 and D7200) have been capturing all-sky images almost every night from September to March with a temporal resolution of less than one minute at Ramfjordmoen Research Station in Tromsø, Norway (69.6 • N, 19.2 • E); the station is operated by the UiT -the Arctic University of Norway. These images were not originally planned to be used for a statistical analysis of the auroras, as they were obtained to evaluate weather conditions during the acquisition of atmospheric temperature/wind observations using a sodium LIDAR [37][38][39][40] and multi-wavelength observations of auroras using a photometer [41][42][43] . The digital cameras used were D5000 during 2010-2014, D5100 during 2015, and D7200 during 2016-2021.…”
Section: Optical Observations In Tromsø Norwaymentioning
confidence: 99%
“…Scourfield et al (1971) proposed a procedure for estimating the emission altitude of PsA using the lifetime of O( 1 S) excited state atoms seen in the optical observations. Since the transition from O( 1 S) to O( 1 D) producing 557.7 nm emission is forbidden and its lifetime is about 0.70 s, time-series of the 557.7 nm emission exhibits a systematic time lag compared to that of an allowed transition emission such as 427.8 nm, whose lifetime is ~ 10 −8 s (Nozawa et al 2018). Scourfield et al (1971) estimated the altitude of the 557.7 nm emission from this delay time because the delay time is longer at higher altitudes.…”
Section: Open Accessmentioning
confidence: 99%
“…In the current statistical analysis, we employed the fivewavelength photometer (Nozawa et al 2018) and Electron Multiplying Charged Coupled Device (EMCCD) all-sky camera both of which have been operative in Tromsø, Norway (69.6N, 19.2E, 66.7MLAT). The fivewavelength photometer has the field-of-view (FOV) of about 0.98 degrees and measures the auroral emissions in the field-aligned direction at 5 wavelengths simultaneously (427.8 nm, 557.7 nm, 630.0 nm, 777.4 nm, 844.6 nm).…”
Section: Datasetsmentioning
confidence: 99%
“…In the PsA event by Nozawa et al (2018), it was found that there was a time delay between emissions in the 427.8 (70-ns lifetime) and 557.7 nm (0.7-s lifetime), but there was no time delay between emissions in the 427.8 and 630.0 nm (110-s lifetime or shorter at lower heights). The time delay in the 557.7 nm would be explained by the longer lifetime of OI 557.7 nm, compared with that of 427.8 nm.…”
Section: 1029/2020ja028250mentioning
confidence: 99%
“…Liang et al (2016) conducted PsA observations with 3‐s cadence by a high sensitive imager equipped with a bandpass‐filter for 630.0 nm and found PsA‐related modulations in the 630.0‐nm emission intensity. PsA observations with 400‐Hz data sampling rate using a multi‐wavelength photometer (Nozawa et al, 2018) showed pulsations in the 630.0‐nm channel, in addition to pulsations in the 427.8 nm ( N2+ 1NG (0,1)), the 557.7 nm (OI 557.7 nm), and so on. It is noted that the lifetimes of N2+ 1NG and OI 557.7 nm are 70 ns (i.e., prompt emission) and 0.7 s, respectively (cf.…”
Section: Introductionmentioning
confidence: 99%